Analysis Of The Effect Of Service Quality On Costumer Satisfaction At Mr. Beauty Store, Takalala Branch, Soppeng - Puji Rahmah; Muhammad Alamsyah Ramli (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This research was conducted at Mr. Beauty Store, Takalala Branch, located in Takalala, Tettikenrarae Sub-district, Marioriwawo District, Soppeng Regency. The sampling technique used was Quota Sampling, resulting in a sample of 100 customers from Mr. Beauty Store, Takalala Branch. To determine the effect of service quality on customer satisfaction, a simple linear regression analysis technique was used. Based on the results of the regression analysis and the discussion conducted, it can be concluded that service quality has a positive and significant effect on customer satisfaction at Mr. Beauty Store, Takalala Branch. The better the quality of service provided, the higher the level of customer satisfaction, which in turn can increase customer loyalty and repeat purchases. As an effort to continuously improve customer satisfaction, the management of Mr. Beauty Store, Takalala Branch is advised to continue enhancing service quality through employee training, improving service speed and responsiveness, and implementing consistent service standards to meet and exceed customer expectations